Governing the GM crop revolution: policy choices for developing countries - Paarlberg, Robert L. (International Food Policy Research Institute, 2000)
Will developing countries adopt policies that promote the planting of genetically modified (GM) crops, or will they select policies that slow the spread of the GM crop revolution? The evidence so far is mixed. In some prominent countries such as China, policies are in place that encourage the independent development and planting of GM crops. Yet in a number of other equally prominent countries the planting of GM crops is not yet officially approved. The inclination of developing countries to promote or block the spread of GM crops can be judged by the policy choices they make in five separate areas: intellectual property rights (IPR) policy, biosafety policy, trade policy, food safety policy, and public research investments. Paarlberg discusses various policy options related to GM crops: (1) Intellectual Property Rights; (2) Biosafety; (3) Trade; (4) Food Safety and Consumer Choice; and (5) Public Research Investments. The appropriate policies for each of these must be adopted by developing countries.